Entre justicia y moralidad: criterios metateóricos en cuanto a la justicia, la moral y el derecho (2016)
The social advance of the last decades implies the need to rethink various legal schemes and the way they are integrated into contemporary society. For this reason, human dignity, human rights and the democratic principle, which serves as their foundation while, at the same time, limiting them too, must be assumed as political and legal values for the sake of collective development. This means the subjection of powers and institutions to the Constitution and to fundamental rights in diverse private and public spheres that individuals must handle, such as the social, cultural, and political spheres.